Conceptual review of the connection between emotional intelligence and physical activity - Zurita Ortega, F.; Moreno Arrebola, R.; González Valero, G.; Viciana Garófano, V.; Martínez Martínez, A.; Muros Molina, J. J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
At present the knowledge of the physical and cognitive aspects is essential in the sport context, before this situation the image that a person has about himself (self-concept) and how he is emotionally (emotional intelligence) has repercussions on sports action. Given this situation, the following work is proposed with the intention of examining the number of studies in the Web of Science that contain the terms self-concept and emotional intelligence along with the parameters physical activity and sport, in both Spanish and English. The results showed that there was a greater number of articles in English than in Spanish, and studies related to self-concept are more numerous than those of emotional intelligence, and when searching for works that contain all of the aforementioned parameters, in Spanish no Jobs are detected, while in English sixteen appear.